The Role of Civil Society Organisations in Asset Recovery - Maguchu, Prosper; Ghozi, Ahmad (Indonesian Journal of International Law, 2022)
In Zimbabwe, civil society organisations (CSOs) have played a significant role in documenting cases of corruption and mismanagement that have deprived Zimbabweans of their basic human rights. This work can facilitate asset recovery efforts, which is a high priority for the Government of Zimbabwe. The country continues to face enormous challenges despite the political changes that have occurred in recent years. This makes the contribution of civil society all the more important. In particular, CSOs can play a role in raising public awareness, research, advocacy, case management and monitoring returned assets. Hence, CSOs should not only be encouraged but also equipped to work with government and state institutions: providing information, increasing accountability and building political will. The government and third sector can achieve far more working cooperatively than either could alone. To that end, Transparency International Zimbabwe seeks to provide CSOs with a platform to effectively engage with and support the recovery of stolen assets within and beyond Zimbabwe’s borders. This paper will encourage CSOs to explore opportunities to effectively engage in the asset recovery process, including in partnership with other actors, so that they can work towards returning the assets to Zimbabweans in desperate need. As the first of its kind, this paper is not intended to be exhaustive, but rather provides an introductory overview to CSOs’ engagement with asset recovery and identifies their specific strengths. It also analyses CSOs’ asset recovery networks, which will allow Transparency International Zimbabwe to understand who is already working with whom so that it can build on this knowledge for future collaborations. In terms of scope, this paper discusses asset recovery in the context of corruption-related offences, with an emphasis on cases involving senior public officials.